Decoupled Roles for the Atypical, Bifurcated Binding Pocket of the ybfF Hydrolase. Issue 9 (13th May 2013) - Ellis, Elizabeth E.; Adkins, Chinessa T.; Galovska, Natalie M.; Lavis, Luke D.; Johnson, R. Jeremy
Abstract Serine hydrolases have diverse intracellular substrates, biological functions, and structural plasticity, and are thus important for biocatalyst design. Amongst serine hydrolases, the recently described ybfF enzyme family are promising novel biocatalysts with an unusual bifurcated substrate‐binding cleft and the ability to recognize commercially relevant substrates. We characterized in detail the substrate selectivity of a novel ybfF enzyme from Vibrio cholerae (Vc‐ybfF) by using a 21‐member library of fluorogenic ester substrates. We assigned the roles of the two substrate‐binding clefts in controlling the substrate selectivity and folded stability of Vc‐ybfF by comprehensive substitution analysis. The overall substrate preference of Vc‐ybfF was for short polar chains, but it retained significant activity with a range of cyclic and extended esters. This broad substrate specificity combined with the substitutional analysis demonstrates that the larger binding cleft controls the substrate specificity of Vc‐ybfF. Key selectivity residues (Tyr116, Arg120, Tyr209) are also located at the larger binding pocket and control the substrate specificity profile. In the structure of ybfF the narrower binding cleft contains water molecules prepositioned for hydrolysis, but based on substitution this cleft showed only minimal contribution to catalysis. Instead, the residues surrounding the narrow binding cleft and at the entrance to the binding pocket contributed significantly to the folded stability of Vc‐ybfF. The relative contributions of each cleft of the binding pocket to the catalytic activity and folded stability of Vc‐ybfF provide a valuable map for designing future biocatalysts based on the ybfF scaffold.